ABCG2 c.421C>A polymorphism alters nifedipine transport to breast milk in hypertensive breastfeeding women - Malfará, Bianca Nayra [UNESP]; Benzi, Jhohann Richard de Lima; de Oliveira Filgueira, Gabriela Campos; Zanelli, Cleslei Fernando [UNESP]; Duarte, Geraldo; de Carvalho Cavalli, Ricardo; de Moraes, Natália Valadares [UNESP] (Elsevier, 2019)
Nifedipine, a known substrate to breast cancer resistance protein (ABCG2/BCRP), is used for the treatment of hypertension during breastfeeding. This study aimed to evaluate the effect of ABCG2 c.421C>A on nifedipine transfer to breast milk (BM) in hypertensive women. Nineteen hypertensive breastfeeding women treated with 20 mg nifedipine every 12 hours were investigated. Blood and BM samples were collected simultaneously 15–30 days after delivery and at least 15 days after drug treatment. Patients genotyped as ABCG2 c.421CC showed nifedipine plasma and BM concentrations ranging from 8.32–178.1 ng/mL and 4.8–58.5 ng/mL, respectively. ABCG2 c.421C>A showed a trend towards significance (p = 0.0793) on nifedipine in BM, with concentrations approximately 3 times higher in the heterozygous 421 CA (29 ng/mL) in comparison to 421 CC (10.5 ng/mL). Nifedipine BM/plasma ratio was significantly lower in 421CC when compared to 421CA (p = 0.01). In conclusion, ABCG2 c.421C>A polymorphism is associated with higher transfer of nifedipine to BM.
Keywords: Breast cancer resistance protein; Breast milk; Hypertension; Nifedipine